Rancang Bangun Alat Peraga Axial Flow Turbine Dengan Menggunakan Tenaga Electrical Sebagai Media Pembelajaran AMTO - James Siregar; Lalu Giat Juangsa Putra; Rizky Pratama Hudhajanto; Dicky Reza Prawira (Jurnal Teknologi dan Riset Terapan (JATRA), 2021)
Aircraft maintenance is very important in aviation safety. Therefore, ICAO (International Civil Aviation Organization) strictly regulates the people who can carry out the maintenance process. To be able to become a mechanic or engineer who maintains aircraft, it is necessary to have 3 stages, namely the basic certificate, type rating and AMEL (Aircraft Maintenance Engineering License). Currently in Indonesia there are only 13 AMTO (Aircraft Maintenance Training Organizations) that can issue the certificate. AMTO schools are limited because the facilities required by the authorities are very high and expensive. One of these facilities is a turboprop engine, a type of generator aircraft engine that uses a gas turbine to drive the propeller. The high cost of the training equipment facilities, which can reach hundreds of millions or even billions, gave rise to the idea to make a simple teaching aid about turboprop systems in general, namely the Axial Flow Turbine which applies the concept of a turboprop engine where the propeller can rotate due to mechanical motion from the gear that comes from the DC motor. Manufacture of Axial Flow Turbine components using lathe, and milling. The materials used are iron, plastic, and rubber. The Axial Flow Turbine can produce a maximum rpm of 200 rpm. After passing the maximum limit, the propeller's ability to rotate will decrease significantly. In the end, the Axial Flow Turbine teaching aid can be used as a learning medium, especially the turboprop system.